Analisis Faktor Yang Memengaruhi Kejadian Gastritis Diruang Rawat Inap RSUD Kota Baubau Tahun 2020 - Laode Swardin; Rahmawati Azis; Muhammad Farid (2021)
Gastritis is an inflammatory process of the mucous lining and the gastric sub-mucosa. Gastritis is one of the most common diseases in the clinic in general (Slamet, 2014). Research aims to determine the analysis of factors that affect the incidence of gastritis in the inpatient room of Baubau General Hospital year 2020 .This research is the type of research used is quantitative research, using cross sectional design. Cross sectional study is a study to learn the dynamics of correlation between factors related to the effect by way of approach, observation or data collection at one time (point time approach) with sample 71 respondents who were in the hospitalization of the city Hospital.The results of the study of the economic status (P = 0.000) of diet (P = 0.028) smoking (P = 0.000) stress (P = 0.000) that there is a significant influence on economic status, diet, smoking, stress on the incidence of gastritis in the inpatient Room General Hospital of Baubau year 2020 while Smoking is the dominant factor incidence of gastritis in the inpatient Hospital of Baubau 2020. Advice in this research as a material input and information about the incidence of gastritis for the Hospital so that can conduct health promotion regarding the prevention of the incidence of gastritis. With the results of this study is expected to sufferers to be able to pay attention to the meal time according to the meal schedule especially breakfast time, day and night and reduce and avoid the types of foods that can cause gastric acid to increase such as spicy food and acid respondents are also expected to avoid factors that can trigger the occurrence of stress as well as many activities that can be able to act on stress such as sports and religious activities and avoid or reduce the number of cigarettes smoked in a day.